Improving Winter Wheat Yields In Organic Farming Systems Through Innovations In Green Manure Management (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents effect of perennial grasses (Trifolium pratense L., Medicago sativa L., xFestulolium) and their aboveground mass management methods (removed from the field, mixed, mulching) as preceding crops on Ninorg in the soil as well as on yield of winter wheat under conditions of ecological farming. Field experiments were carried out at the Joniškėlis Research Station of the Lithuanian Institute of Agriculture (LIA) on an Gleyic Cambisol. Experimental evidence indicated that content of symbiotically fixed nitrogen in the biomass of legumes accounted for the largest share (61–84 %) of the total nitrogen content (208.0–298.0 kg ha- 1), accumulated in the biomass. Winter wheat grain yield significantly (r = 0.783; P < 0.05) correlated with soil inorganic nitrogen content in spring. Grain yield productivity increased by 0.01 t ha-1 after incorporation of 1 kg ha-1 nitrogen of legume crops biomass.